Mapping the effects of international trade on economic growth of South Africa: Econometric review (Journal of Academic Finance, 2025)
Purpose: The purpose of this study is to investigate the effects of international trade on the economic growth of South Africa.Method: The study employed the autoregressive distributed lag (ARDL)  approach for 50 years, from 1973 to 2022 and annual time series data from the World Bank database.Results: The study results revealed that South Africa economic growth is subsequent to the purchasing power parity theory and Heckscher-Ohlin theory, by highlighting that international trade is used to drive a higher inflation and to increase the level of exchange rate. There is evidence that South Africa has adopted measures that causes loss of value on the currency and economic growth in general.Originality: The novelty of this study lies in the fact that the South African government must be considerate and sensible when creating international trading strategies by aligning the relevant real interest rate that will assist to monitor international trade channels and policies to enhance and sustain future economic growth. This study contributed to the understanding of the effects of international trade on economic growth debate particularly, by prompting the level of trade to drive South African economic growth to reach the desired level. Keywords: economic growth, international trade, developing countries, ARDL approach, South Africa
Keywords: economic growth; international trade; developing countries; ARDL approach; South Africa